DISIPLIN APARATUR SIPIL NEGARA TERHADAP KINERJA PEGAWAI PADA BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SULAWESI TENGAH - Pratama, Zainal Bakti; Ariani, Nora (Jurnal Metaverse ADPERTISI, 2024)
The purpose of the study is: to find out and analyze how the work discipline of employees in BPSDM Central Sulawesi Province, and to find out the factors that become obstacles and supporters and alternative solutions. In this study, researchers used basic survey research and qualitative descriptive research types. Researchers set the location of the research at the office of the Human Resources Development Agency (BPSDM) of Central Sulawesi Province. With the population in this study is the entire State Civil Apparatus and Honorary Personnel totaling 125 people. The sampling technique using purposive sampling is to assign 31 people. Data collection techniques use 4 (four) ways, namely, Observation, Interview, Questionnaire, and Documentation, while analysis techniques use frequency and percentage tables. The results showed that Civil Apparatus Discipline measured from high Responsibility was considered unfavorable. To use office equipment properly and observance of office rules is seen as good. For performance variables measured, quality and quantity indicators are considered less good while task implementation is considered good. The supporting factor in this study is that all employees in working use office equipment with a sense of responsibility and after each work all equipment used is stored in its original place properly and tidied up. All employees have followed the rules set by both clothing (uniform) and attributes and office rules asking permission if they do not enter the office or have business outside the office. The inhibiting factor in this study is that there are still many employees who are less responsible in completing the tasks given so that the quality of work is not good in carrying out tasks.